2005
DOI: 10.1097/01.ta.0000187813.79047.42
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Decision Instrument to Guide Computed Tomographic Imaging of Blunt Head Injury Patients

Abstract: Clinical characteristics can reliably identify patients who are unlikely to have intracranial injuries and who do not require CT imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
131
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 16 publications
2
131
1
2
Order By: Relevance
“…The design and patient characteristics of the 19 studies (representing 22 articles) 26,27,29,46,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] that evaluated the diagnostic performance of clinical decision rules for identifying ICI or need for neurosurgery in adults with MHI are summarised in Table 2. Eight studies were from the USA, 27,29,55,58,59,61,62,64 two each from Italy, 54,57,71 Canada 26,46 and the Islamic Republic of Iran, 66,67 and one each from the Netherlands, [68][69][70] Australia, 65 Japan, 63 Spain 60 and Denmark.…”
Section: Clinical Decision Rules Description Of Included Studies Adultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The design and patient characteristics of the 19 studies (representing 22 articles) 26,27,29,46,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] that evaluated the diagnostic performance of clinical decision rules for identifying ICI or need for neurosurgery in adults with MHI are summarised in Table 2. Eight studies were from the USA, 27,29,55,58,59,61,62,64 two each from Italy, 54,57,71 Canada 26,46 and the Islamic Republic of Iran, 66,67 and one each from the Netherlands, [68][69][70] Australia, 65 Japan, 63 Spain 60 and Denmark.…”
Section: Clinical Decision Rules Description Of Included Studies Adultsmentioning
confidence: 99%
“…Eight studies were from the USA, 27,29,55,58,59,61,62,64 two each from Italy, 54,57,71 Canada 26,46 and the Islamic Republic of Iran, 66,67 and one each from the Netherlands, [68][69][70] Australia, 65 Japan, 63 Spain 60 and Denmark. 56 Six were multicentre studies.…”
Section: Clinical Decision Rules Description Of Included Studies Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Similar sensitivity and specificity are given for the New Orleans Criteria, National Emergency X-Ray Utilization Study-II, and Miller Criteria. 5,15,16 More recent studies compared the specific CT head rules with the aim of finding the best rule to reduce the number of ordered CT scans. Stiell et al reevaluated their 2001 study prospectively and found that the use of the CCHR in patients with head trauma resulted in a CT rate of 52.1%.…”
mentioning
confidence: 99%